1997
DOI: 10.1002/hep.510250317
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mutation and deletion of the tumor suppressor gene CDKN2A (MTS1/p16) in hepatocellular carcinoma from an Australian population

Abstract: comprises multiple cumulative genetic alterations, consistent The tumor suppressor gene CDKN2A (MTS1/p16), lowith the multistage nature of all late onset cancers, 5 which cated on chromosome 9p21, is inactivated in a variety of has been well investigated in colorectal cancer. tumors including melanomas and tumors of the biliaryThe multiple genetic alterations that occur in human cantract, pancreas, and stomach. The aim of the present cer target both oncogenes and tumor suppressor genes. 7 Tustudy was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…Inactivation of this gene has been found in a variety of human cancers caused by different mechanisms, including mutation, homozygous deletion of MTS1/p16 loci or hypermethylation of 5 CpG island [25][26][27]. In our specimens, the 9p21-p23 showed high frequency of genetic alteration, but somatic mutation of MTS1/ p16 was infrequent in primary hepatic carcinoma, a finding similar to that found among Australian population [28]. The most common mechanism of silencing the p16 gene in HCC may be due to de novo hypermethylation of 5 CpG island [26], [27].…”
Section: Discussionsupporting
confidence: 85%
“…Inactivation of this gene has been found in a variety of human cancers caused by different mechanisms, including mutation, homozygous deletion of MTS1/p16 loci or hypermethylation of 5 CpG island [25][26][27]. In our specimens, the 9p21-p23 showed high frequency of genetic alteration, but somatic mutation of MTS1/ p16 was infrequent in primary hepatic carcinoma, a finding similar to that found among Australian population [28]. The most common mechanism of silencing the p16 gene in HCC may be due to de novo hypermethylation of 5 CpG island [26], [27].…”
Section: Discussionsupporting
confidence: 85%
“…Although LOH on the p16 region is common in various types of tumors, yet the reported LOH in HCC showed varying frequencies (Kita et al, 1996;Biden et al, 1997;Chaubert et al, 1997). In addition, LOH on chromosome region 9p21 in HCC has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…By using two polymorphic markers¯anking the 9p21 region (IFNA and D9S126), Kita et al (1996) reported 17.9% of the HCC from Japan had LOH on 9p21. On the other hand, Biden et al (1997), used eight polymorphic markers¯anking the same region, detected LOH in 44% of the HCC samples from Australia. Using a larger number of HCC cases and more microsatellite markers, our study showed the highest frequency of LOH (60.4%) on 9p21 region in HCC which is in accordance with results from other types of cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation of the p16 INK4 promoter leading to the absence of protein expression was found in 30-70% of the tumors (Liew et al, 1999;Matsuda et al, 1999;Jin et al, 2000;Weihrauch et al, 2001). Somatic inactivating mutations and homozygous deletions of the gene are rarely observed in HCC (Biden et al, 1997;Jin et al, 2000). Finally, Gankyrin was found to be overexpressed in all cases of 34 analysed HCC (Higashitsuji et al, 2000).…”
Section: )mentioning
confidence: 99%